Discourse and practice in human geography - Erica Schoenberger (Geografares, 2024)
This article examines the way in which our disciplinary discourse shapes our material practices as researchers and our ways of thinking. It uses as a case study the term ‘competitiveness’, considering its origins and meanings within economics and business, the way these are imported into our own work, and the consequences of an unexamined acceptance of the validity and meaning of the term. The article works through two examples of discourse in action, asking to what degree Nike’s ‘competitiveness’ depends on access to low-cost labour in offshore production sites, and whether the ‘competitiveness’ of Baltimore would be harmed by adopting the ‘living wage’ as the local minimum. The article argues the necessity of analysing ourselves as social and historical actors and assessing the way we work and the way we use language in order to strengthen our research and improve the standing of the discipline.